Extracellular Vesicles Tropism: A Comparative Study between Passive Innate Tropism and the Active Engineered Targeting Capability of Lymphocyte-Derived EVs - Tania Limongi (MDPI AG, 2021)
Cellular communications take place thanks to a well-connected network of chemical–physical signals, biomolecules, growth factors, and vesicular messengers that travel inside or between cells. A deep knowledge of the extracellular vesicle (EV) system allows for a better understanding of the whole series of phenomena responsible for cell proliferation and death. To this purpose, here, a thorough immuno-phenotypic characterization of B-cell EV membranes is presented. Furthermore, the cellular membrane of B lymphocytes, Burkitt lymphoma, and human myeloid leukemic cells were characterized through cytofluorimetry assays and fluorescent microscopy analysis. Through cytotoxicity and internalization tests, the tropism of B lymphocyte-derived EVs was investigated toward the parental cell line and two different cancer cell lines. In this study, an innate capability of passive targeting of the native EVs was distinguished from the active targeting capability of monoclonal antibody-engineered EVs, able to selectively drive the vesicles, enhancing their internalization into the target cancer cells. In particular, the specific targeting ability of anti-CD20 engineered EVs towards Daudi cells, highly expressing CD20 marker on their cell membrane, was proved, while almost no internalization events were observed in HL60 cells, since they did not express an appreciable amount of the CD20 marker on their plasma membranes.